Trends in Florida Citrus with Emphasis on Indian River, St. Lucie, Martin, and Palm Beach Counties - Jackie K. White; P.J. van Blokland (EDIS)
FE636, a 9-page fact sheet by Jackie K White and P.J. van Blokland, examines how hurricanes, freezes, citrus diseases and pests, competition with Brazil, and a booming population growth are affecting the citrus industry of Florida's Treasure Coast. It also examines the efforts of governments, organizations, and individuals to respond quickly and efficiently to these threats to the area's agricultural lands. Published by the UF Department of Food and Resource Economics, June 2006.